EDUCATORS' UNDERSTANDING OF THE CONCEPT OF INCLUSIVE EDUCATION IN PRIMARY SCHOOLS IN SOUTH AFRICA - Zakhele Dennis Nzuza (Indonesian Journal of Learning and Instruction)
This study explores educators’ understanding of the concept of inclusive education in South African primary schools. The study draws on thorough research and reflective engagements over the past twenty years on the promulgation of inclusive education in South Africa. Despite various policies being introduced and adopted by the South African government, understanding of the concept of inclusive education remains a contested issue in the education sector. Therefore, this study aims to deepen the core of the understanding and practices of the inclusive education concept. A case study design using a qualitative approach was used in the four primary schools in uMgungundlovu District, South Africa, to elicit a deeper understanding of inclusive education as a concept and practice within general education. The collected data were analysed using thematic analysis. The study findings revealed that educators’ understanding of inclusive education was largely informed on the basis of respect and confidence by which learners experiencing learning barriers develop their abilities to the best of their potential. The educators’ understanding was anchored on positive attitudes toward inclusive education as a concept of education. However, the study findings also showed that the understanding of inclusive education by some educators was based on referring learners experiencing learning barriers to special schools. The study recommends that educators should attend intensive training at institutions of higher learning to fill the gap in understanding and practice of inclusive education.